Digital entrepreneurship and its impact on digital supply chains: The mediating role of business intelligence applications - Heba Awawdeh (Growing Science, 2022)
This study aimed to test and evaluate the impact of Digital Entrepreneurship and its impact on digital supply chains in Jordanian hotels, and the mediating role of digital supply chains in this relationship. The descriptive analytical method was used, and the study population consisted of (835) male and female employees, and a random sample was used with a simple random sample of (342) participants. To achieve the objectives of the study, a developed questionnaire was used to collect data from the sample members. The study adopted the Statistical Package for Social Sciences (SPSS.V.22) and Structural Equations Modeling (SEM) using the AMOS program for path analysis and to perform statistical analysis using: Descriptive and inferential statistics measures, including Multiple linear regression, Pearson correlation coefficient, skew coefficient, multiple linear correlation, variance inflation coefficient and permissible variance. The study reached results, the most important of which were: The most important results of the study were: the presence of an important impact of Digital Entrepreneurship in digital supply chains and the presence of a significant impact of Digital Entrepreneurship through business intelligence applications as an intermediate variable in digital supply chains. The study recommends the need to enhance Digital Entrepreneurship in Jordanian hotels by focusing on the holistic view of these hotels and their environment, whether the internal environment that focuses on strengths and weaknesses in the hotel’s capabilities or their external environment that brings opportunities and challenges.